An Experimental Test of a Search Model under Ambiguity - Takao Asano; Hiroko Okudaira; Masaru Sasaki (Institute for the Study of Labor (IZA), 2014)
This paper's objective is to design a laboratory experiment to explore the effect of ambiguity on a subject's search behavior in a finite-horizon sequential search model. In so doing, we employ a new approach to observe the potential trend of reservation points that is usually unobserved. We observe a significant dip in a trend of reservation points when subjects are faced with ambiguity over wage distributions.
Keywords: C91; D81; 330; experiment; search model; ambiguity; reservation wage